Key technologies and system development for regional integrated energy system - Cong Zhang; Ke Peng; Yu Han; Li Wang; Shunqi Zeng; Wenjie Dong (Energy Reports, 2020)
To combat energy shortage, RIES has become an important research direction in the international energy field. In order to improve energy efficiency and the large-scale consumption of renewable energy, this paper presents the key technologies of RIES, which consists of the coupling relationship, the applicability of control equipment for multi-energy systems and the principle of fault handling. Furthermore, a control system for RIES is designed and discussed in software architecture and data processing. The simulation and practical results indicate that it can effectively deal with the unexpected situation of RIES.
Keywords: 330; Coordinated control; Energy coupling; Regional integrated control system; Regional multi-energy system